2017
DOI: 10.3390/ma11010038
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Synthesis, Stability, and Thermal Conductivity Properties of Water-Based SnO2/Reduced Graphene Oxide Nanofluids

Abstract: With the rapid development of industry, heat removal and management is a major concern for any technology. Heat transfer plays a critically important role in many sectors of engineering; nowadays utilizing nanofluids is one of the relatively optimized techniques to enhance heat transfer. In the present work, a facile low-temperature solvothermal method was employed to fabricate the SnO2/reduced graphene oxide (rGO) nanocomposite. X-ray diffraction (XRD), thermogravimetric analysis (TGA), X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…Agarwal et al [132] found that for maximum stabilization of nanofluid the oleylamine to GNP mass ratio is 0.6. [168] ZPT N/A Sodium dodecyl sulfate, sodium dodecyl benzene sulfonate, dodecyl betaine [169] ZPT, PSD~ 30 days N/A [174] UV-Vis~ 60 days N/A [175] ZPT, SPC~ 2 months N/A [176] Sedimentation balance method~ 34 days N/A [179,180] UV-Vis, ZPT~ 15 days Sodium deoxycholate [183] UV-Vis~ 10 days N/A [184,189] SPC, ZPT~ 3 months N/A [190] ZPT~ 60 days N/A [196] ZPT N/A N/A Fig. 13 Electrostatically and sterically stable nanoparticles [215] For electrostatic stabilization, the existence of surface charge or Coulomb repulsion is a major source of stabilization.…”
Section: Stability Mechanismsmentioning
confidence: 99%
“…Agarwal et al [132] found that for maximum stabilization of nanofluid the oleylamine to GNP mass ratio is 0.6. [168] ZPT N/A Sodium dodecyl sulfate, sodium dodecyl benzene sulfonate, dodecyl betaine [169] ZPT, PSD~ 30 days N/A [174] UV-Vis~ 60 days N/A [175] ZPT, SPC~ 2 months N/A [176] Sedimentation balance method~ 34 days N/A [179,180] UV-Vis, ZPT~ 15 days Sodium deoxycholate [183] UV-Vis~ 10 days N/A [184,189] SPC, ZPT~ 3 months N/A [190] ZPT~ 60 days N/A [196] ZPT N/A N/A Fig. 13 Electrostatically and sterically stable nanoparticles [215] For electrostatic stabilization, the existence of surface charge or Coulomb repulsion is a major source of stabilization.…”
Section: Stability Mechanismsmentioning
confidence: 99%
“…Several researchers have also reported improving nanofluid thermal conductivities with increasing temperature, and suggest increasing Brownian motions of the suspended nanoparticles as a possible mechanism 66 , 67 . Since increasing Brownian motions tends to promote micro-convection, which in turns enhances local mixing 68 , 69 .…”
Section: Resultsmentioning
confidence: 97%
“…The reduced graphene oxide crystallization peaks in the XRD pattern of SnO 2 /rGO are lack. The order of the reduced graphene oxide plane is disrupted by the SnO 2 particles, or reduced graphene oxide sheets are inserted into the SnO 2 lattice [ 48 ]. SnO 2 /rGO has the advantages of two materials.…”
Section: Resultsmentioning
confidence: 99%